Antimicrobial alternatives to control pathogens involved in liver abscesses, food safety and mastitis in cattle - Schnur, Sydney E. (Kansas State University, 2021)
Antimicrobial agents are used to treat and prevent bacterial infections. In cattle, antimicrobials are most often used to control, treat, or prevent respiratory disease and liver abscesses in feedlot cattle and mastitis in dairy cows. Liver abscesses occur in feedlot cattle because of feeding an energy dense, high grain diet. The primary causative agent is Fusobacterium necrophorum, a ruminal bacterium that enters portal circulation to reach the liver and cause abscesses. Currently, in-feed tylosin is widely used to reduce the incidence of liver abscesses. Mastitis, an economically important disease of dairy cows, is caused by a number of bacterial pathogens, mainly Staphylococcus aureus, Streptococcus agalactiae, S. dysgalactiae, S. uberis, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Escherichia coli. Beta-lactams, macrolides (erythromycin), and lincosamides are the common antimicrobials used for mastitis prevention and treatment. Additionally, foodborne illnesses are a major public health concern and food animals are major carriers of many foodborne pathogens. Three major foodborne bacterial pathogens that reside in the gut and are shed in the feces of cattle are Shiga toxin-producing E. coli, Salmonella enterica, Campylobacter jejuni, and C. coli. The most common antimicrobials used to treat Salmonella and Campylobacter infections in humans are fluoroquinolones, macrolides, cephalosporins, and diaminopyrimidine plus sulfa drug combinations. Antimicrobial resistance (AMR) to antimicrobials, particularly to medically important antimicrobials, such as cephalosporins, fluoroquinolones, and macrolides, are a major public health concern. Antimicrobial resistance occurs in pathogens as well as in commensals. Because of a clear association between antimicrobial use and emergence of AMR, there are efforts to restrict and minimize the use of antimicrobials, and at the same time, if possible, replace with antimicrobial alternatives. In my studies, I have focused on the following three antimicrobial alternatives: bacteriophages, clustered regularly interspaced short palindromic repeats (CRISPR) with CRISPR-associated proteins (Cas), and sorghum grain phenolic extract. Therefore, the main objectives were to evaluate the potential of bacteriophages, CRISPR-Cas9, and phenolic extracts of sorghum grains to inhibit major pathogens of liver abscesses, mastitis, and foodborne illnesses associated with cattle. Bacteriophages are viruses that infect bacteria and cause them to lyse (lytic bacteriophages) and are known for their host specificity. Therefore, we hypothesized that bacteriophages could be an effective tool to selectively target and eliminate or reduce the concentration of F. necrophorum in the rumen, thereby minimizing the chance for it to cross the ruminal epithelium to reach the liver to cause abscesses. Studies were conducted to isolate and characterize bacteriophages lytic to F. necrophorum. Pooled bovine ruminal fluids from slaughtered cattle at abattoirs and untreated city sewage samples were collected on five separate dates. A total of 68 F. necrophorum subsp. necrophorum strains of liver abscess origin were used to isolate bacteriophages. Aliquots of pooled ruminal fluid or sewage samples were incubated anaerobically overnight with lysine and subsp. necrophorum strains. The aliquots were then filtered, bacteria-free filtrates were spotted on lawns of the strains, and presence of plaques were considered as positive for phages. Presumptive bacteriophage plaques were harvested, and the viruses were purified by serial passaging on the susceptible bacterial strains. The bacteriophage isolation frequencies were compared between sample types, sampling dates, and F. necrophorum strains. The overall relative frequency of isolated bacteriophages lytic to F. necrophorum subsp. necrophorum was 17.1 %. The frequency of bacteriophage isolation between collection dates ranged from 0 to 25.4 % for ruminal fluid, and from 13.7 to 32.0 % for sewage samples. The frequency of isolation of bacteriophages lytic to F. necrophorum subsp. necrophorum from sewage samples was higher (p < 0.0001) than lytic bacteriophages isolated from bovine ruminal fluid samples. Bacteriophages were isolated more frequently with certain F. necrophorum subsp. necrophorum strains than others. The characterization of the isolated bacteriophages included determination of host specificity, electron microscopic morphology, development of insensitivity, and optimal pH and temperature stability. All 25 bacteriophages were lytic to F. necrophorum subsp. necrophorum only and did not lyse subsp. funduliforme or any of the other bacterial species tested. Based on morphology determined by transmission electron microscopy, twenty bacteriophages belonged to Siphoviridae, Myoviridae, or Podoviridae families. Four bacteriophages with icosahedral heads and no tail and one with multiple tails could not be unclassified. In broth cultures, 11 bacteriophages inhibited F. necrophorum subsp. necrophorum up to 12 hrs, while the other 14 bacteriophages only slightly slowed the growth of the bacterium. F. necrophorum subsp. necrophorum became insensitive to all 11 lytic bacteriophages after 24 h. At a pH of 2.5, all 11 bacteriophages were inactivated immediately, while at a pH of 3.5, six bacteriophages were only partially inactivated upon initial exposure and five survived for 1 hr. Between pH 4.5- pH 8.5, no reduction in bacteriophage activity was observed. After 24 h of incubation at 30 °C, 40 °C, and 50 °C, lytic activities of the 11 bacteriophages were unaffected. Bacteria use RNA-guided (gRNA) CRISPR-Cas systems to protect against foreign nucleic acids, particularly mobile genetic elements, including bacteriophages. Because CRISPR-Cas systems can be used to modify genetic material by precisely cutting target nucleotides, we hypothesized that the system could be used to inhibit F. necrophorum in the rumen or liver. The concept was first tested in E. coli with plasmids that had the F. necrophorum rpsP gene inserted. A 1.3- to 3.3-log₁₀ reduction was observed when the rpsP gene was targeted from a plasmid in E. coli. The approach was then used to cleave the fomA gene that encodes an outer membrane protein in F. necrophorum. This resulted in a 1.0- to 3.6-log₁₀ reduction in bacterial cell concentrations. However, the Cas9 control reduced bacterial cell concentrations by 2.0-log₁₀ in F. necrophorum. This observation was not seen in E. coli. This could be because F. necrophorum has an endogenous CRISPR-Cas type I system. More studies should be conducted to determine how this endogenous system works and to further determine if CRISPR-Cas systems are possible antimicrobial alternatives to tylosin in cattle production. Phenolic compounds have antimicrobial properties, and some specialty sorghum grain varieties are high in phenolic compounds. Therefore, sorghum grain phenolic extract may have the potential to be used as a natural antimicrobial alternative. The antimicrobial effects of sorghum phenolic extract on bacterial pathogens that cause bovine mastitis and human foodborne illnesses were determined. Bacterial pathogens tested included Shiga toxin-producing Escherichia coli, Salmonella Typhimurium, Campylobacter jejuni, C. coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, K. oxytoca, Staphylococcus aureus, and Enterococcus faecalis. Antibacterial activities of sorghum phenolic extracts at concentrations of 0, 100, 200, 500, 1,000, or 4,000 [mu]g/mL were determined by agar well diffusion assay. Plates were incubated for 18-24 hours and the diameter of each zone of inhibition was measured. The results indicated that sorghum phenolic extract inhibited Staphylococcus aureus, Enterococcus faecalis, Campylobacter jejuni, and Campylobacter coli.
Keywords: Liver abscesses; Antimicrobial alternatives; Cattle; Fusobacterium necrophorum; Bacteriophages; CRISPR-Cas